Private equity challenge: potential leveraged buyout of AUGA group - Costa, Alvaro Miguel Pereira da (2022)
This Investment Committee Paper was performed by a group of students from the Master’s in Finance Program, being intended for academic purposes only. The core objective of this work project is to assess AUGA’s attractiveness as an LBO target. The group elaborated a value creation strategy and an operating model for the investment proposal, backed by a full-blown company and market evaluation, and by the company’s valuation. The group suggested an optimal capital structure for the transaction and possible exit strategies, deriving potential returns for the fund on the exit year. This individual paper will focus on Valuation, Capital Structure, Returns and Due Diligence.